Perkembangan Tindak Pidana Korupsi Masa Kini dan Pengembalian Kerugian Keuangan Negara - Husin Wattimena (IAIN Ambon, 2017)
Corruption is one of the extraordinary crime (extraordinary crime) which endanger the stability and security and economic development in Indonesia. The application of additional punishment in the form of indemnification of the country can be enforced effectively under the provisions of article 18 of Law No. 31 of 1999 on Corruption Eradication jo. Law No. 20 of 2001 on the Amendment of Act No. 31 of 1999 on Corruption Eradication. The results showed that the application of additional punishment in the form of indemnification of countries have applied, but can not become effective on the Ambon District Court jurisdiction. It is based on data of corruption cases in 2014 were 18 cases increased to 30 cases in 2015. The return loss of the state in the year 2014 to 2015 amounted to Rp. 3884029516, - (three billion, eight hundred and eighty-four and twenty-nine thousand five hundred rupiahs), of corruption in 2014-2015. As for corruption in 2014-2016 until now there has been no loss to the state refund deposited into the state treasury Rp. 384 029 516 (three hundred and eighty-four and twenty-nine thousand five hundred rupiah. Obstacles in the implementation of the court judgment on the indemnification of the country is a treasure convict who has changed hands, and the length of judicial proceedings until a decision has permanent legal force